PFM Design under Capacity Constraints : Planning Public Financial Management Reforms in Pacific Island Countries - World Bank; International Monetary Fund (World Bank, Washington, DC, 2013)
This note is intended to inform Public Financial Management (PFM) reform in small Pacific Island Countries (PICs). PFM systems in PIC contexts are often very different from the sophisticated and comprehensive systems operating in larger, wealthier countries. The authors give two key messages. Firstly, PFM capacity should be prioritized to areas that matter most in achieving development outcomes, and reforms should be intended to address specific, identified, problems, rather than to achieve blueprint good practice standards. Secondly, with small numbers of staff and high staff turnover limiting potential for sustainable gains from standard capacity building solutions (such as training programs and workshops), broader options for meeting capacity gaps should be considered, including accessing ongoing support for specialized tasks or even the wholesale outsourcing of certain functions. The three main sections of this note are as follows: (i) how to plan PFM reforms, including through the development of PFM roadmaps; (ii) how to prioritize limited PFM reform capacity to address the most pressing constraints to development; and (iii) how to access additional capacity to implement and sustain required PFM reforms.